INTERPRETASI KECEPATAN GELOMBANG GESER (VS) PADA LAPISAN BAWAH PERMUKAAN DAERAH ‘X’ DENGAN METODE SEISMIK MASW (MULTICHANNEL ANALYSIS OF SURFACE WAVE) - Daud, Anye Gidalti; Lepong, Piter; Natalisanto, Adrianus Inu (GEOSAINS KUTAI BASIN, 2021)
ABSTRACT MASW or Multichannel Analysis of Surface Wave is a seismic method that utilizes the dispersive property of surface wave to interpret surface wave velocity which is directly related to the stiffness of a subsurface layer reaching 30 meters depth that beneficial in the geoengineering field. The goal of this research is to interpret shear wave velocity of subsurface layer in an area to inform the stiffness level of - subsurface layer through shear wave velocity and depth profiling. The steps of this research are converting seismic raw data into numeric data, generating dispersion image, extracting dispersion curve from dispersion image and analyzing dispersion curve by theoretical and experimental data. Based on analysis results, shear wave velocity obtained up to 170m/s with 16 meters investigation depth. Whereas fundamental mode frequency of Rayleigh wave between 2 – 12 Hz. Low shear wave velocity (<180 m/s) of investigated area indicates that the subsurface layer dominated with soft soil which is an early sediment in the shape of alluvium layer and has high seismic wave amplification that hazardous for building build upon the layer.